Investing in Our Faculty: Creative Virtual Recognition Ideas for Leadership - Celine S Hall; Nikki L Williams (Academic Chairpersons Conference Proceedings, 2022)
Faculty are one of our greatest assets. Feeling valued and appreciated by leadership and peers help cultivate feelings of belonging and encourage engagement. In this presentation, we will share ways in which leadership recognizes faculty achievements and provide opportunities for peers to do so as well within an online setting.
Keywords: Recognition; engagement; faculty; online